2002
DOI: 10.1089/10755530260511838
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Resonance Technology™: Scientific Foundation and Summary of Biologic and Clinical Studies

Abstract: Sympathetic Resonance Technology (SRT; Clarus Products, International, L.L.C., San Rafael, CA) is a novel technology used in consumer health care products to protect humans from the potentially harmful effects of stress. A summary of the previously unpublished studies on SRT, both basic and clinical, is presented. These studies collectively show that SRT mitigates the stress response for a variety of stressors such as chemical and electromagnetic stress in various biologic systems and multiple levels of organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Previous studies on a variety of living systems exposed to known stressors have shown that the stress response was measurably decreased by SRT. A variety of protective effects from SRT to various environmental stressors have been shown, including protection of fibroblast cultures, reduced oxidative stress in the blood of humans, decreased acupuncture meridian stress, reduced state anxiety scores in school children, 7 and electroencephalograph stabilization in humans. 8 The present study tests new and improved generation technology derived from SRT produced by the same inventors, Robert O. Williams and Patti Leach, who digitized it using a proprietary method.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies on a variety of living systems exposed to known stressors have shown that the stress response was measurably decreased by SRT. A variety of protective effects from SRT to various environmental stressors have been shown, including protection of fibroblast cultures, reduced oxidative stress in the blood of humans, decreased acupuncture meridian stress, reduced state anxiety scores in school children, 7 and electroencephalograph stabilization in humans. 8 The present study tests new and improved generation technology derived from SRT produced by the same inventors, Robert O. Williams and Patti Leach, who digitized it using a proprietary method.…”
Section: Introductionmentioning
confidence: 99%
“…7,9–12 The term “biofield” (or “bio field”), a medical subject heading at the U.S. National Library of Medicine since 1995, describes the biologic field of the organism proposed to be dynamic and integrative (integrating numerous sources of endogenous and exogenous fields via the superposition principle). The biofield is comprised of electromagnetic, electric, magnetic, and acoustic fields.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations